Identification of Factors For The Acceptance of The SIBANTER Application (Non-Cash Assistance System For Motor Vehicles) By Kir Test Service Users at The Karanganyar Regency Transportation Office - Aisyah Nurcahyaningrum; Priyanto Susiloadi (Jurnal Administrasi Publik, 2025)
The low compliance of vehicle owners, weak supervision, and manual services that are slow and prone to extortion remain challenges in the implementation of vehicle roadworthiness tests (uji kir). Sibanter (Non-Cash Motor Vehicle Assistance System) is an innovation in vehicle testing services at the Karanganyar Regency Transportation Agency, which has been simulated since 2019. This application is designed to facilitate the process of application submission, scheduling, and monitoring of kir inspections online. However, until 2024, the adoption of Sibanter Application still faces various obstacles, so its development goals have not been fully achieved. This study aims to identify the factors influencing user acceptance of the Sibanter Application by applying the UMEGA model (Unified Model of Electronic Government Adoption). The research employed a quantitative method with PLS-SEM analysis, involving 96 respondents selected through convenience sampling, and data were collected via questionnaires. The results indicate that the acceptance of Sibanter Application is influenced by four factors: effort expectancy, social influence, facilitating conditions, and attitude.